2014
DOI: 10.1007/s00404-014-3381-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of borderline ovarian tumors: single center experience of 183 cases

Abstract: In our study, we evaluated a large data pool of 183 patients diagnosed with borderline epithelial ovarian tumors. BOTs have a relatively better prognosis than invasive epithelial ovarian cancer. Surgery with proper staging is the cornerstone of treatment. Patients with BOTs at the early stage can undergo fertility sparing surgery with close follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…In the present study, we found that surgical procedure (radical vs. conservative) was not an independent prognostic factor for DFS or OS. These findings were similar to those of previous studies [ 13 , 18 , 19 ]. We also demonstrated that hysterectomy had no impact on survival in BOT patients, similar to Menczer et al’s study [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that surgical procedure (radical vs. conservative) was not an independent prognostic factor for DFS or OS. These findings were similar to those of previous studies [ 13 , 18 , 19 ]. We also demonstrated that hysterectomy had no impact on survival in BOT patients, similar to Menczer et al’s study [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Total abdominal hysterectomy and bilateral salpingo-oophorectomy (BSO) have been regarded as the standard treatment for BOT [ 22 24 ]. In this analysis, the most common recurrent site is the ovary (75%), consistent with findings from previous studies [ 25 , 26 ]. In addition, the univariate analysis showed that a fertility-sparing procedure was a significant risk factor for patient relapse.…”
Section: Discussionsupporting
confidence: 92%
“…For BOTs, consensus has also not been reached on the indications and roles of adjuvant chemotherapy. This treatment method has not been identified in this study or in previous studies as a significant favorable factor for the prognosis of patients with BOTs [ 15 , 26 ]. Trope et al [ 37 ] demonstrated that adjuvant therapy showed no prognostic benefit but had serious toxicity.…”
Section: Discussionmentioning
confidence: 78%
“…In another study, increased serum CA125 levels were recorded in 40% of the patients diagnosed as stage 1 BOT and 83% of those with advanced-stage BOT ( 10 ). However, studies on other serum tumor markers including CA19-9, CA15-3 and CEA are not available ( 11 ). In our study, we detected higher serum CA-125 levels in eight patients (upper limit of normal=35 U/mL)…”
Section: Discussionmentioning
confidence: 99%